2011
DOI: 10.1103/physrevlett.106.018301
|View full text |Cite
|
Sign up to set email alerts
|

Relativity and the Lead-Acid Battery

Abstract: The energies of the solid reactants in the lead-acid battery are calculated ab initio using two different basis sets at non-relativistic, scalar relativistic, and fully relativistic levels, and using several exchange-correlation potentials. The average calculated standard voltage is 2.13 V, compared with the experimental value of 2.11 V. All calculations agree in that 1.7-1.8 V of this standard voltage arise from relativistic effects, mainly from PbO2 but also from PbSO4. PACS numbers: 82.47.Cb,82.60.Cx,31.15.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 29 publications
2
70
0
6
Order By: Relevance
“…One can also observe relativity in everyday life, e.g., the yellow color of gold and the liquidity of mercury [135]. The lead-acid battery, which is commonly used in cars, strongly relies on the effects of relativity [138]. As put by Pyykkö "relativistic effects in chemistry are more common than you thought" [135].…”
Section: Some Aspects Of Relativistic Quantum Chemistrymentioning
confidence: 99%
“…One can also observe relativity in everyday life, e.g., the yellow color of gold and the liquidity of mercury [135]. The lead-acid battery, which is commonly used in cars, strongly relies on the effects of relativity [138]. As put by Pyykkö "relativistic effects in chemistry are more common than you thought" [135].…”
Section: Some Aspects Of Relativistic Quantum Chemistrymentioning
confidence: 99%
“…145 For silver metal, the corresponding absorption does not occur until 3.7 eV which is already in the ultraviolet. 144 Regarding the origin of the very large relativistic contribution to the lead -acid battery voltage, 6 most of the effect has been traced back to the oxidative power of solid PbO 2 which, in turn, is related to the particular stabilization of the unoccupied Pb 6s levels in the solid due to relativistic effects. Regarding the quintuple bond in U 2 , Gagliardi and Roos noted in their article that, based on their spin-orbit CASPT2 calculations, U 2 affords three fully developed electron-pair bonds, one σ and two π , with the latter formed by combinations of 6d and 5f uranium orbitals.…”
Section: Gold Mercury Lead Umentioning
confidence: 99%
“…Recently, Ahuja et al showed that spin-orbit coupling is required to accurately reproduce certain reaction energies in lead-containing compounds. 56 The reaction energies studied by Ahuja et al, involved a metal and two oxides with different oxidation states. Our simpler reactions (involving only oxides in a Pb 2+ oxidation state) do not show major errors with lead-containing compounds (see Figure 4 and Table II).…”
mentioning
confidence: 99%